Study of Community Perceptions of Green Open Spaces in Samarinda City - Danish Naira Irawan; Yulian Widya Saputra; Aisyah Trees Sandy; Rahmadi Rahmadi (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
Green Open Space (GOS) in Samarinda City plays an important role as an ecological buffer, recreational facility, and public social space. However, variations in quality, facilities, and management have raised concerns about public comfort and the use of these spaces. This study aims to analyze public perceptions of Green Open Spaces in Samarinda City by examining user characteristics, utilization patterns, and comfort levels. The research applied a descriptive quantitative method using a questionnaire survey distributed to visitors of several major green open spaces, including Samarendah Park, Smart Park (Edupark), Bebaya Park, and Teras Samarinda. The results show that the majority of respondents perceive green open spaces as very important and generally rate their overall condition as good. Cleanliness, safety, and the availability of supporting facilities were identified as the main factors influencing public comfort and perception. These findings indicate that continuous improvement in the quality and management of green open spaces is essential to enhance community comfort and optimize their utilization.